2013
DOI: 10.1159/000347043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index, Surgical Approach and Lymphadenectomy on the Development of Symptomatic Lymphoceles after Radical Prostatectomy

Abstract: Purpose: Identification of factors influencing lymphocele formation requiring intervention after radical prostatectomy. Methods: 302 patients undergoing radical retropubic prostatectomy (RRP, n = 174) or transperitoneal robot-assisted laparoscopic prostatectomy (RALP, n = 128) by the same surgeon were retrospectively reviewed. Incidence of symptomatic lymphoceles (SLC) was compared with clinical and pathological data (contingency analyses, Wilcoxon-Kruskal-Wallis test). Results: Sixteen patients (5.3%) develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
3
13
2
1
Order By: Relevance
“…Our data did not support this hypothesis. A number of other authors also couldn't find any influence of age [20,26,27] .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our data did not support this hypothesis. A number of other authors also couldn't find any influence of age [20,26,27] .…”
Section: Discussionmentioning
confidence: 90%
“…Mundhenk et al reported that the lymphocele-positive cohort had a significantly higher BMI than their lymphocele-negative counterparts [20] . This is the only study so far to show this connection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be more representative for patients undergoing RP in Tyrol, a multicentre study approach should be considered. Additionally, an assessment of further complications of RP could be done [34]. Finally, our study does neither differentiate between different surgical approaches for RP (i.e., open, laparoscopic and robot-assisted) nor compare the number to patients with prostate cancer not undergoing RP or patients who are candidates for active surveillance [35].…”
Section: Discussionmentioning
confidence: 99%
“…Its potential link to prostate cancer (PCa), which is the most common malignancy in men in developed countries and the second most common worldwide, has attracted many clinicians' attention [8,9,10,11]. As a result, a large body of literature has been recently published, with three quarters of the world's publications written over the last decade [12].…”
Section: Introductionmentioning
confidence: 99%